A survey of beliefs, attitudes, knowledge, and behaviors about evidence-based practice in physical therapists of Latin America: a cross-sectional study - Marco Antonio Morales-Osorio; Leidy T. Ordoñez-Mora; Héctor Gutiérrez-Espinoza; Felipe Araya-Quintanilla; Ana Bays-Moneo; Robinson Ramírez-Vélez (Scientific Reports)
Abstract Evidence-based practice (EBP) refers to the integration of scientific evidence into the clinical setting. This study aimed to determine whether Latin American physiotherapists use EBP, analyze the associated factors, barriers, and facilitators, and examine the relationships between these elements in clinical practice. To conduct this cross-sectional study, the web-based questionnaire survey method was chosen. Survey was self-administered questionnaires to assess understanding of various EBP-related terms and determine their knowledge and ability to apply these concepts in clinical practice. The association between attitudes, awareness, and knowledge scores and the demographic data such as age group, years of experience, professional membership registry, and self-reported education was assessed. The questionnaire was distributed to a total of 5000 physical therapists, of which 4099 (82%) responded from seven Latin American countries (Argentina, Bolivia, Chile, Colombia, México, Perú, and Venezuela), between June 1, 2020, and May 31, 2024. Overall, the physical therapists had positive attitudes, beliefs, and interests in EBP. Their educational background, knowledge, and skills related to assessing and interpreting information were associated to the use of EBP. In addition, 53% of respondents indicated that lack of time was the main obstacle to the use of EBP. The top 3 barriers included insufficient time (53%), lack of information resources (20.8%), and lack of research tools (13.6%). Among Latin American physical therapists, individual characteristics workplace, clinical experience, educational background, and demographic characteristics, may behave as facilitators or barriers when performing an EBP. Thus, identifying methods and strategies to support physical therapists in adopting EBP in the Latin American is necessary. The academization of physiotherapy training might change this in the future.